TWO-YEAR TREND OF OUT-OF-HOSPITAL CARDIAC ARREST IN BOSNIA AND HERZEGOVINA - Alihodzic, Hajriz; Jevtić Drkić, Tatjana (Journal Resuscitatio Balcanica, 2024)
ABSTRACT: Introduction: Participating in research under the auspices of the International Liaison Committee on Resuscitation /ILCOR - available data on out-of-hospital cardiac arrest /OHCA- Out-of-hospital cardiac arrest/ for 2016 and 2017 from Bosnia and Herzegovina were collected. Methods : We invited the voluntary participation of all emergency medical services in the collection of OHCA data in 2015-2017 in Bosnia and Herzegovina/BiH/. We received descriptive data on the most important elements of the latest recommendations of the Utstein form for 2016 and 2017 from Sarajevo Canton and Tuzla. Results: The research in BiH in 2016 covered 417,498 or 12.0% of the total population, and in 2017 it covered 529,521 or 15.0%. The annual incidence of OHCA in Bosnia and Herzegovina treated by emergency medical services in 2016 was 75.4, in 2017 it was 65.0 per 100,000 inhabitants. Provision of cardiopulmonary resuscitation /CPR/ by eyewitnesses was 2.9% in 2016 and 4.1% in 2017. Emergency medical care witnessed OHCA in 2.2% of patients in 2016 and 7.3% in 2017. Survival of OHCA until discharge from the hospital or 30-day survival of patients who were treated by emergency medical assistance in BiH was 12.7% in 2016, 7.8% in 2017. Conclusion: We observed that there are no national or local registers of out-of-hospital cardiac arrest in accordance with the Utstein recommendations. The extremely low number of CPR initiated by eyewitnesses affects the total number of survival to discharge from the hospital and the 30-day survival of the patient.